Prospective case–control study on pain intensity after the use of promethazine in patients undergoing videothoracoscopy - Zhou, Xiangwei; He, Benhui; Zheng, Xia; Li, Chao; Mi, Zeyu; Peng, Mingqing; Li, Min (Frontiers in Medicine, 2024)
Objective Effective and secure pain management following video-assisted thoracoscopic surgery (VATS) is crucial for rapid postoperative recovery. This study evaluated analgesic and sedative effects of sufentanil and promethazine in patient-controlled intravenous analgesia (PCIA) post-thoracic surgery, along with potential adverse reactions. Methods In this prospective, randomized, controlled, double-blind, clinical study, 60 patients (American Society of Anesthesiologists status I–III) undergoing VATS were enrolled. The patients were randomized into experimental (Group P) or control (Group C) groups. PCIA was administered post-general anesthesia using a double-blind method. Group P received sufentanil (3 μg/kg) + promethazine (1 mg/kg) + 0.9% sodium chloride solution (100 mL total), while Group C received sufentanil (3 μg/kg) + 0.9% sodium chloride solution (100 mL total). PCIA settings included a 1-mL bolus and 15-min locking time. The primary outcomes were the visual analog scale (VAS) at rest and during coughing and sedation (Ramsay) scores at 6, 12, 24, and 48 h. The secondary outcomes were rescue drug use rate, hemodynamic parameters (mean arterial pressure and heart rate), percutaneous oxygen saturation, respiratory rate, and occurrence of adverse reactions. Results Group P exhibited lower resting and coughing VAS scores at 6, 12, 24, and 48 h, plus decreased incidence of nausea and vomiting within 48 h post-surgery compared with Group C (p < 0.05). No significant differences were observed in pruritus, sedation (Ramsay) scores, mean arterial pressure, heart rate, oxygen saturation, or respiratory rate between the two groups (p > 0.05). Discussion The combination of sufentanil and promethazine for postoperative intravenous analgesia could effectively reduce adverse effects such as nausea and vomiting, contributing to postoperative pain relief.